PLANT ECOLOGY AND THE LAW OF THE RELATIONSHIP BETWEEN ACTION AND RESULT: . - Kishora Swain , Braj (Journal of Dharma, 1991)
It is good to introduce the topic with a reference to Newton’s famous third law of motion, according to which for every action there is an equal and opposite reactlon.’ But the special point of view presented in this paper, is the link between that Law. Translated into the moral realm, and its associated concept of rebirth with plant ecology.